Everyday Sexuality and Social Work: Locating Sexuality in Professional Practice and Education - Priscilla Dunk (Social Work and Society)
Social work has seen increased intellectual interest in sexuality. However, little attention has been paid to the relevance of everyday sexuality for professional practice or how this might be integrated within existing social work curricula. This paper proposes that knowledge about everyday sexuality is vital to social workers as they deal with a variety of clients faced with the increasing complexities brought about by late-modernity. Additionally, it is argued that this knowledge base is congruent with the ethical and political dimensions of the profession. The PLISSIT model is presented as a possible pedagogical framework for social work education in this area.